PREPARATION OF LOW TEMPERATURE TiO2 PHOTO ELECTRODE FOR FLEXIBLE DYE SOLAR CELLS APPLICATION - Lia Muliani; Erlyta S R; Jojo Hidayat; Shobih Shobih; Mariya AlQibtiya (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2013)
PREPARATION OF LOW TEMPERATURE TiO2 PHOTO ELECTRODE FOR FLEXIBLE DYE SOLAR CELLS APPLICATION. Flexible dye solar cells were dye cell that were assembled using plastic transparent electrodes as substrate, so the cell processing must be applied in low temperature. In this paper, investigation of TiO2 photo electrode preparation will be described. We used a low temperature TiO2 paste which deposited onto Indium Tin Oxide-PolyEthylene Terephthalate (ITO-PET) substrate using doctor blade printing technique. The annealing temperature of the TiO2 layer was 120 oC, 130 oC and 140 oC for 4 hours. The optical properties were investigated by Ultra Violet-Visible Spectrophotometer. The performance of the cell was measured using a solar simulator with light at an intensity of 50 mW/CM2 generated by a xenon lamp. An efficiency of 0.019 % was achieved for such cells with a 2.0 cm2 active area under TiO2 annealed in 120oC.